HUMAN-AI COMMUNICATION: SIGN INTERPRETATION CHALLENGES AND CONTEXTUAL UNDERSTANDING IN DIALOGUE (Journal of Universal Science Research, 2025)
This study presents an in-depth analysis of the sign interpretation mechanisms that are found within human and AI interaction using semiotics, cognitive and neurolinguistics, as well as pragmatics perspectives. Research conducted brings to light important critical issues such as the specificity of AI in syntactic and semantic text analysis, or issues regarding processing polysemous words and cultural codes, or even avenues through which AI can handle pragmatic intent interpretation. Particular emphasis is given to analyses of the issues related to cultural noise and intercultural communication problems in automated dialogues, along with their implications on the effectiveness of communication.